A Brief Comment on "Percent Change as a Measure of Price Escalation in Water and Energy Utilities" by Jordi Honey-Rosés and Claudio Pareja. (October 2019) - Hanser, Philip
This comment discusses the article by Honey-Roses and Pareja (2019). It attempts to provide additional insights into their analysis by placing it in a price index framework. A simple example is provided, which demonstrates this alternative view along with other suggestions for the use of their analysis.